Cognitive-Interactionist and Socio-Cultural Perspective of Corrective Feedback: A research synthesis - fadilah, eka (Dinamika : Jurnal Sastra dan Budaya, 2019)
Abstract This paper aims at synthesizing the utilization of corrective feedback second/foreign language (S/FL) teaching. I schewed on a three-main-tenet of corrective feedback seen from its forms, task instruction, timing, and mediating variables. As such, I encompassed this paper into four subsequent steps: Reviewing and synthesizing, finding the discrepancies, and recommending. First is reviewing and synthesizing. In this step, I collected some papers pertaining to two schools of corrective feedback perspective: cognitive interactionist (e.g., recasts) and socio-cultural (e.g., scaffolded feedback) perspectives. Second is unveiling the discrepancies to resolve. After getting such discrepancies, efforts in resolving are highlighted both in the two types of CF. Later, suggestion and recommendation are elucidated later.Key words: corrective feedback, cognitive-interactionist perspective, socio-cultural perspective